RELEVANSI KONSEP ZUHUD DALAM TASAWUF TERHADAP GAYA HIDUP KONSUMTIF MASYARAKAT MODERN - Miswar Rasyid Rangkuti; Taufik Hidayat (STKIP Subang, 2026)
The rapid development of modern society has encouraged the emergence of a consumptive lifestyle characterized by excessive purchasing behavior, material orientation, and the pursuit of social status. This condition potentially weakens spiritual values and moral awareness. Therefore, the concept of zuhud in Sufism becomes highly relevant as a spiritual approach that emphasizes simplicity, self-control, and prioritizing eternal values over temporary worldly pleasures. This study aims to analyze the relevance of the concept of zuhud in Sufism as an ethical and spiritual solution to the consumptive lifestyle in modern society. This research employs a qualitative approach using library research methods by analyzing classical and contemporary Sufi literature, supported by sociological studies on consumer culture. Data were analyzed using descriptive-analytical techniques to examine the correlation between Sufi values and modern lifestyle behavior. The results show that zuhud does not mean rejecting the world entirely, but rather controlling attachment to material possessions and using wealth proportionally according to needs. The application of zuhud values can encourage individuals to develop self-awareness, gratitude, simplicity, and social responsibility, which can reduce excessive consumption patterns. Therefore, the concept of zuhud in Sufism remains highly relevant as a moral foundation in shaping a balanced, ethical, and spiritually oriented lifestyle in modern society.